Quantitative regional placental shear wave elastography for prediction of composite adverse neonatal outcomes in third-trimester preeclamptic pregnancies: a prospective Egyptian cohort study - Manar M Sayed; Nasr M. Osman; Reem Ahmed; Saad El Gelany; Sara M. Sayed; Shimaa Shehata Elsharkawy (Egyptian Journal of Radiology and Nuclear Medicine, 2026)
Abstract Background Preeclampsia is a major cause of maternal and neonatal morbidity and mortality with a prevalence in Egypt (6–10.7%) exceeding global averages. Beyond conventional Doppler assessment, placental dysfunction occurs at a microstructural level that may not be detected by macrovascular indices. Shear wave elastography (SWE) enables quantitative assessment of placental stiffness; however, its regional heterogeneity and prognostic relevance to neonatal outcomes remain insufficiently explored. Objectives This study evaluated the novel role of regional placental SWE mapping, with particular focus on the maternal-central placental region, for predicting composite adverse neonatal outcomes in preeclamptic pregnancies, and compared SWE values between preeclamptic and low-risk pregnancies across disease severity subgroups. Methods A prospective study was conducted including 88 third-trimester pregnancies (44 preeclampsia, 44 controls). SWE was performed using a systematic regional mapping approach, assessing maternal-central, maternal-peripheral, fetal-central, and fetal-peripheral placental regions. Diagnostic performance was evaluated using ROC analysis and correlation with composite neonatal outcomes. Results Placental stiffness was significantly increased in preeclamptic pregnancies across all regions ( p < 0.001), with a distinct regional gradient, most pronounced in the maternal-central region. This region demonstrated the highest diagnostic performance for neonatal outcomes AUC of 0.88 (95% CI 0.80–0.96) and strongest correlation with composite adverse neonatal outcomes ( r = 0.58, p < 0.001). At an exploratory cut-off > 20.0 kPa, it achieved 84.2% (95% CI 65.3–93.6) sensitivity, 88.9% (95% CI 78.8–94.5) specificity, and 86.4% (95% CI 77.7–92.0) accuracy. SWE values also increased significantly with disease severity ( p < 0.05), supporting a dose–response relationship between placental stiffness and clinical severity. Conclusions Regional placental SWE mapping, particularly of the maternal-central zone, offers added diagnostic value over global placental assessment for predicting composite adverse neonatal outcomes in preeclampsia. SWE values increased significantly with disease severity, supporting its role as a marker of disease burden, and may serve as a quantitative biomarker for risk stratification pending validation in larger, multicenter cohorts.